Biochemistry in undergraduate health courses: Structure and organization - Silva, Irani F.; Batista, Nildo A. (Biochemistry and molecular biology education, 2003)
This article describes the following aspects of teaching biochemistry in undergraduate health courses: objectives, number of hours, time in which the subject is studied, selection of content, teaching strategies, and evaluation methodologies used. Fifty‐three courses distributed in 13 areas within the health field and offered by 12 institutions were analyzed for this matter. An exploratory research was developed, with data obtained from documentation analysis, form completion, and interviews with teachers involved. For the analysis of data, both quantitative and qualitative approaches were used. The analysis of teaching plans for the subjects under investigation shows that their inclusion in the curriculum occurs early in the professional education. The subject focus is intradisciplinary, and there is a great diversity in terms of number of hours, even if one looks at the same professional field. There is a tendency to standardize objectives, centralizing the teaching in “biochemical knowledge,” which is frequently not related to the specific proposal of professional education. We also noticed that there is a certain degree of similarity in the contents, even though some specific content is seen in the courses of dentistry and veterinary medicine. From the value given to lectures, one could see an evidence of transmission of pre‐established content. Thus, there seems to be a need to stimulate the use of more active learning methodologies. As for evaluation, this study suggests an increased emphasis on the formative approach to assessing students.